Explaining participation in the Colorado Republican River and Nebraska Platte-Republican Resources Area Conservation Reserve enhancement programs - Monger, Randall Grant, author; Suter, Jordan, advisor; Manning, Dale, committee member; Schneekloth, Joel, committee member (Colorado State University. Libraries, 2016)
Agricultural land retirement is increasingly used to conserve groundwater resources, reduce challenges associated with the conjunctive use of water resources, and meet streamflow compliance. This study explores the factors that influence the participation of agricultural producers in the Colorado Republican River and Nebraska Platte-Republican Resources Area Conservation Reserve Enhancement Programs (CREP). A better understanding of what leads agricultural producers to enroll in CREP could be used to inform program managers on how changing the incentives offered or expanding eligible area would impact enrollment and ultimately groundwater conservation. We develop a theoretical model of CREP participation using a random utility framework that contains the incentives offered for participation, measures approximating the opportunity costs of participation, and aquifer and soil characteristics. We then construct a dataset of participating wells and eligible non-participating wells and generate spatial measures of the explanatory variables. We empirically investigate participation using Probit models, which are estimated with data from the three basins aggregated and also each basin separately. The sign on many of our estimated significant coefficients varies across the three models. For the three participation models, we find that an increase in saturated thickness decreases the probability of participating in CREP.